(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The concept of “Lusitanian” and “Lusitania” stands stably only with the creation of a Roman province with this name. So far these words change their meaning over time and according to the different ancient authors, creating misunderstandings. This situation, with consequences in modern historiography, becomes more complex by the variety of the approaches. Historiography, linguistics and archeology do not coincide in the territory to which these concepts must be applied. Therefore, some principles that should governed the use of these terms are proposed.